Synthetically encapsulated & self-organized transition metal oxide nano-structures inside carbon nanotubes as robust: li-ion battery anode materials - Kapoor, Aakanksha; Patrike, Apurva L.; Singh, Nitesh; Thauer, Elisa; Ottmann, Alexander; Klingeler, Rüdiger; Ogale, Satishchandra; Bajpai, Ashna (Journal of physics. D, Applied physics, 2023)
We report a comparative study on the electrochemical performance of four different transition metal oxides encapsulated inside carbon nanotubes (oxidesCNT), along with reference data obtained on a bare-oxide. A key result here is that the encapsulation leads to superior cyclic stability, irrespective of the type of the oxide-encapsulate. This comparison also enables us to isolate the advantages associated with the encapsulation of oxide within the core cavity of CNT, as opposed to the case of oxide/CNT composites, in which oxide resides outside the CNT. Innovative use of camphor during sample synthesis enables precise control over the morphology of the filled CNT, which can either be in aligned-forest or in entangled geometry. The morphology appears to play a crucial role in tuning the magnitude of the specific capacity, whereas the encapsulation relates to the cyclic stability. Overall, the electrochemical data on various oxides@CNT bring forward interesting inferences pertaining to the morphology, filling fraction of the oxide-encapsulate, and the presence of oxide nano-particles adhering outside the CNT. Our results provide useful pointers for optimization of these critical parameters, thus paving the way for oxide@CNT for practical electrochemical applications.